Existential Threats to Nepal’s National Security: A Strategic and Multidimensional Analysis - Baniya, Suresh Kumar (Journal of Development and Administrative Studies, 2025)
The paper examines the characteristics of existential threat on national security in Nepal as dynamic and multi-dimensional and not confined to conventional military paradigm. The conceptualization of existential risk adopted in the study is based on the modern security literature, which regards those sluggish but accretive forces as the erosion of governance, economic dependency, fragmentation, environmental stress, and the geopolitical constraint. Nepal as a state whose historical interpretation has been positioned between India and China makes it especially valuable in understanding how the interaction of these overlapping vulnerabilities acquires new security calculus to small, landlocked states in the twenty-first century. The study design applied in the study involves qualitative and multi-source study design through the use of semi-structured interviews with the elites, national policies reports, protest reports around the 2025 youth mobilizations, and secondary governance and strategic information. Thematic repetition was used to code these materials, and text-mining tools, e.g., frequency and cluster analysis, were used to supplement the interpretive results in order to triangulate interpretive results. This interconnectedness resulted in six theatres which encompass transformation of security paradigm in Nepal, political oligarchy, governance and youth mobilization deficits, economic instability, anthropogenic and systemic risks and geopolitical vulnerability. The combination of these pressures develops what the study calls layered fragility a scenario in which institutional weakness, social disgruntlement, climate pressure and reliance on foreign aid mutually intensify each other as time goes by, gradually restricting state capacity and strategic freedom. It suggests that the processes of compounds and endogenous are more likely to trigger the existential risks to Nepal than the imminent interstate conflict. By assuming it is the interplay of internal vulnerability and external forces that contribute to the anthropogenic threat, and the vulnerability of small states, the article contributes to the security-studies discourse of the need to reform governance, to diversify economies, to adapt to climate change, and to get more people into politics as the foundations of long-term state resilience.